Access for Dummies - Ulrich-Fuller, Laurie 1961-; Cook, Ken (For dummies, 2022)
Become a database boss ...and have fun doing it...with this accessible and easy-to-follow guide to Microsoft AccessDatabases hold the key to organizing and accessing all your data in one convenient place. And you don't have to be a data science wizard to build, populate, and organize your own. With Microsoft Access For Dummies, you'll learn to use the latest version of Microsoft's Access software to power your database needs.Need to understand the essentials before diving in? Check out our Basic Training in Part 1 where we teach you how to navigate the Access workspace and explore the foundations of databases.Ready for more advanced tutorials? Skip right to the sections on Data Management, Queries, or Reporting where we walk you through Access's more sophisticated capabilities. Not sure if you have Access via Office 2021 or Office 365? No worries - this book covers Access now matter how you access it.The book also shows you how to:* Handle the most common problems that Access users encounter* Import, export, and automatically edit data to populate your next database* Write powerful and accurate queries to find exactly what you're looking for, exactly when you need itMicrosoft Access For Dummies is the perfect resource for anyone expected to understand, use, or administer Access databases at the workplace, classroom, or any other data-driven destination